ANALISIS SISTEM PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN KARYAWAN DI KANTOR KESYHABANDARAN DAN OTORITAS PELABUHAN KELAS I BITUNG - Rumondor, Nosevira H. K.; Kalangi, Lintje; Afandy, Dhullo (Universitas Sam Ratulangi, 2018)
Income tax article 21 is the tax applicable for employee. The income of the employee is subject to withholding of Income Tax Article 21, for the company is authorized to withhold the employeeâ€™s income. The purpose of this study is to analyze whether the system of calculation and reporting Income Tax Article 21 has been in accordance with the taxation law and regulation. The research method used is descriptive qualitative method. The results obtained are based on the provision of Object of Income Ta Article 21 according to DGT Regulation PER-16 / PJ / 2016, there is still object of Income Tax Article 21 which has not been collected by the Office of Kesyahbandaran dan Otoritas Pelabuhan Kelas 1 Bitung. In terms of calculations are in accordance with the the Regulation of the Director General of Tax No. PER-16 / PJ? 2016. For the calculation of Â final Income Tax Article 21 are based on Ministry of Finance (MoC) Decree PMK 262 in 2010 for the calculation of Article 21 tax for permanent employees who become the burden state budget. In terms of reporting of Periodic Tax Return, conducted by the State Treasury Office (KPN) through e-filling application on the website of the Directorate General of Taxes and has been in accordance with applicable provisions.Keywords : Income Tax Article 21, employee